1995
DOI: 10.1128/jb.177.3.694-698.1995
|View full text |Cite
|
Sign up to set email alerts
|

Identification of receptor binding sites by competitive peptide mapping: phages T1, T5, and phi 80 and colicin M bind to the gating loop of FhuA

Abstract: Previously we proposed a transmembrane model of the FhuA receptor protein in the outer membrane of Escherichia coli. Removal of the largest loop at the cell surface converted the FhuA transport protein into an open channel and rendered cells resistant to the FhuA-specific phages T1, T5, and 80 and to colicin M. In the present study we employed acetylated hexapeptide amides covering the entire surface loop to investigate binding of the phages and of colicin M. Competitive peptide mapping proved to be a powerful… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
88
1

Year Published

1995
1995
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(91 citation statements)
references
References 21 publications
2
88
1
Order By: Relevance
“…This result refutes the idea that a MAb bound to its surface-located determinant would sterically inhibit the binding of all ligands. Because the determinant recognized by Fhu4.1 is proposed to be linear, it follows that there exists some linear sequence within amino acids 316 to 356 which acts as the determinant for Fhu4.1, despite the requirement for a phage binding region with secondary structure (24). It is possible that the binding of Fhu4.1 to its determinant prevents the inactivation of T5 phage by inducing or preventing a conformational change in FhuA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This result refutes the idea that a MAb bound to its surface-located determinant would sterically inhibit the binding of all ligands. Because the determinant recognized by Fhu4.1 is proposed to be linear, it follows that there exists some linear sequence within amino acids 316 to 356 which acts as the determinant for Fhu4.1, despite the requirement for a phage binding region with secondary structure (24). It is possible that the binding of Fhu4.1 to its determinant prevents the inactivation of T5 phage by inducing or preventing a conformational change in FhuA.…”
Section: Discussionmentioning
confidence: 99%
“…It was proposed that the transmembrane strands of FhuA assume the conformation of a large beta barrel, with the predicted loop of amino acids 316 to 356 forming a ''gate'' that somehow regulates ferrichrome transport through the channel (4,22). Recently, Killmann et al (24) identified amino acids within the proposed gating loop of FhuA which contribute to the binding of phages T1, T5, and 80 and of colicin M. Preincubation of phages or colicin M with selected synthetic hexapeptides representing sequences between amino acids 316 and 356 of FhuA reduced the efficiency of plating of the lethal agents by up to 7 orders of magnitude. It was concluded that three regions of the gating loop were involved in the binding of T1, T5, 80, and colicin M and that the regions probably formed a single binding region for the ligands.…”
mentioning
confidence: 99%
“…T1 and 80 phages interact with the FhuA receptor, and mutational studies have delineated the fixation site on a large external gating loop (residues 322 to 355) (70,341,342). Contrary to Tol-dependent bacteriophages, the viral protein responsible for host (or TonBdependent receptor) recognition has yet to be identified.…”
Section: Reception Of Bacteriophagesmentioning
confidence: 99%
“…It has a large 121,752 bp 80 genome with composition that is typical of members of this genus (Wang et al 2005). T5 infects E. coli by binding to the bacterial ferrichrome transporter, encoded by the FhuA gene, and specifically to its gating loop (Killmann et al 1995). In the course of several terms using …”
Section: Introductionmentioning
confidence: 99%